Application of Slow Stroke Back Massage Module to Reduce Dysmenorrhea in Adolescents - Dina Isfentiani; Rijanto Rijanto; May P. Mendinueto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Introduction Pain during menstruation (dysmenorrhea) is a problem for young women and causes disturbances in daily activities. The pain occurs shortly before or together with the onset of menstruation and lasts several hours although in some cases it can last several days. Analysis of the factors that influence dysmenorrhea, frequency, intensity, time and type of pain in dysmenorrhea can be used as a basis for assessing the dysmenorrhea pain scale. The general objective of this study is to apply a cutaneous stimulation module to reduce dysmenorrhea in adolescents The method is qualitative which is done by looking for the dominant factors that influence the incidence of dysmenorrhea, to make an instrument of theme analysis. The population in this study were students of the Applied Midwifery Study Program with a sample of 46 students who were taken by executive sampling. The dependent variables of this study are the factors that influence dysmenorrhea consisting of age, family history, exercise, junk food habits, frequency of dysmenorrhea, intensity of dysmenorrhea, time of dysmenorrhea, type of dysmenorrhea, while the independent variable is cutaneous stimulation. Data analysis was carried out descriptively, then variable instruments were arranged, FGD (Focus Group Discussion), Expert Consultation and the last was compiling modules. Results age factor is a factor that affects dysmenorrhea in adolescents at the beginning of 84% of adolescents experiencing dysmenorrhea at the age of 13-17 years, while the family history factor is 63% there is a family history of mothers experiencing dysmenorrhea, then adolescents also experience dysmenorrhea. Sports factors can 67% of adolescents experience dysmenorrhea, the most exercise is jogging. Factors of junk food habits 45.7% of teenagers say junk food is the preferred food. The frequency of dysmenorrhea 95.7% of adolescents experience frequent dysmenorrhea in the menstrual cycle. In the intensity of dysmenorrhea, 45.7% of adolescents said the pain picture was of mild and moderate intensity. Time / time of dysmenorrhea found 80% of adolescents said they experienced pain at the beginning of menstruation. the type of adolescent dysmenorrhea is 98% type / type of dysmenorrhea with a primary. age factor is a factor that affects dysmenorrhea in adolescents at the beginning of 84% of adolescents experiencing dysmenorrhea at the age of 13-17 years, while the family history factor is 63% there is a family history of mothers experiencing dysmenorrhea, then adolescents also experience dysmenorrhea. Sports factors can 67% of adolescents experience dysmenorrhea, the most exercise is jogging. Factors of junk food habits 45.7% of teenagers say junk food is the preferred food. The frequency of dysmenorrhea 95.7% of adolescents experience frequent dysmenorrhea in the menstrual cycle. In the intensity of dysmenorrhea, 45.7% of adolescents said the pain picture was of mild and moderate intensity. Time / time of dysmenorrhea found 80% of adolescents said they experienced pain at the beginning of menstruation. the type of adolescent dysmenorrhea is 98% type / type of dysmenorrhea with a primary. Discussions. Age factors, family history, exercise habits and consumption habits of junk food scustions of age, family history, exercise habits and consumption habits of junk food are factors that influence dysmenorrhea in adolescents. ages 13-17 emotional/psychological. Jogging is a sport that can increase the pain of dysmenorrhea. The opposite of light exercise such as gymnastics will produce endorphins. Endorphins are neuropeptides that the body produces when relaxed. The habit of consuming junk food for snacks or large meals will make the fat pile up more and more, causing dysmenorrhea. Junk food is a type of food that contains high calories, fat, salt, and oil, but low in vitamins and fiber. Usually, junk food also contains various food additives (BTP) such as sweeteners, flavors and preservatives. Eating too much junk food can lead to an increased risk of being overweight or obese. Adolescents with obesity are at risk for primary dysmenorrhea. The frequency of dysmenorrhea in adolescents is frequent. Adolescents According to Prawirohardjo & Wiknjosastro (2011: 182), dysmenorrhea that occurs in adolescents is usually primary dysmenorrhea. With frequent consumption of junk food and jogging, and supported by family factors, adolescents will often experience dysmenorrhea. The intensity of pain in adolescents is categorized as mild and moderate because adolescents are still able to withstand pain and hormones are still good. The time experienced by adolescents when dysmenorrhea occurs at the beginning of menstruation, the beginning of menstruation is the time when the menstrual blood flow is heavy. Type / type of dysmenorrhea experienced by adolescents is dysmenorrhea with primary type. This type is the type that often occurs in dysmenorrhea in adolescents. Suggestions for young women should be that the cutaneous stimulation module can be used as an alternative solution when experiencing menstruation accompanied by dysmenorrhea and for health care facilities this module can be used as material in providing health education for the community if experiencing dysmenorrhea. pain during dysmenorrhea and non-dysmenorrhea